Controlling a DC Motor through Lypaunov-like Functions and SAB Technique - Alejandro Rincón; Fabiola Angulo; Fredy Hoyos (Institute of Advanced Engineering and Science, 2018)
In this paper, state adaptive backstepping and Lyapunov-like function methods are used to design a robust adaptive controller for a DC motor. The output to be controlled is the motor speed. It is assumed that the load torque and inertia moment exhibit unknown but bounded time-varying behavior, and that the measurement of the motor speed and motor current are corrupted by noise. The controller is implemented in a Rapid Control Prototyping system based on Digital Signal Processing for dSPACE platform and experimental results agree with theory.